Digital fascism - Fuchs, Christian 1976- (Media, communication and society, 2022)
This fourth volume in Christian Fuchs's Media, Communication and Society book series outlines the theoretical foundations of digital fascism and presents case studies of how fascism is communicated online. Digital Fascism presents and engages with theoretical approaches and empirical studies that allow us to understand how fascism, right-wing authoritarianism, xenophobia, and nationalism are communicated on the Internet. Divided into three parts, the book builds on theoretical foundations from key theorists such as Theodor W. Adorno, Franz L. Neumann, Erich Fromm, Herbert Marcuse, Wilhelm Reich, Leo Löwenthal, Moishe Postone, Günther Anders, M.N. Roy, Henry Giroux, and Martin Heidegger. The second part draws on a range of case studies, including Nazis celebrations of Hitler's birthday on Twitter, the 'red scare 2.0' directed against Jeremy Corbyn, Donald Trump, Boris Johnson, and the Austrian presidential election to analyse communication online and in social media. In conclusion, Fuchs argues that slowing down the logic of the media can advance and renew debate culture in the age of digital authoritarianism, fake news, and filter bubbles. Each chapter focuses on a particular dimension of digital fascism or a critical theorist whose work helps us to illuminate how fascism and digital fascism work, making this essential reading for both undergraduate and postgraduate students of media and communication studies, sociology and politics"--Provided by publisher.